Fenomena Fashion K-Pop Sebagai Pembentukan Identitas Diri Remaja di Cikupa,Banten - Yoga, I Komang Dharma; Zuryani, Nazrina; Nugroho, Wahyu Budi (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2023)
The hallyu wave that entered Indonesia has increased teenagers' interest in music, movies/dramas and idols to Korean fashion. Teenagers' interest in K-Pop fashion indirectly makes it a self-identity that is known in the social environment and to recognize themselves. This study analyzes the phenomenon of K-Pop fashion on the formation of self-identity in adolescents in Cikupa, Banten with a qualitative approach method with descriptive-explanatory data. The theoretical analysis used in this research as a scalpel is Stuart Hall's Identity theory. The results of this study reveal that teenager in Cikupa, Banten who use K-Pop fashion can form self-identity through the introduction of enlightenment subjects known in the social environment and recognize themselves. Through sociological subjects when interacting there is recognition when using K-Pop fashion in their social environment indirectly or directly believing in their identity for teenagers in Cikupa, Banten. Postmodern subjects know that the background of teenagers using K-Pop fashion is influenced by the globalization process because they can easily choose or adopt what they like. K-Pop fashion can shape self-identity in adolescents who are identical as their characteristics in their social environment. There are opportunities in the fashion industry that can be used as K-Pop fashion as a reference or elaborated using materials/models that carry the richness of Indonesian culture that are elaborated in K-Pop-style fashion to attract teenagers and K-Pop fandom.